Primary and recurrent ovarian high-grade serous carcinomas display similar microRNA expression patterns relative to those of normal ovarian tissue - Nam, Eun Ji (Oncotarget, 2016)
Most patients with epithelial ovarian cancer eventually die due to recurrence. However, little is known about the microRNA (miRNA) expression pattern and its involvement in recurrent ovarian cancer. We analyzed miRNA expression profiles related to the recurrence of advanced ovarian high-grade serous carcinoma (HGSC) using miRNA microarrays. Between May 2006 and December 2012, 37 ovarian HGSC patients underwent secondary cyto-debulking surgery at recurrence. Among them, only 8 pairs of primary and recurrent tumor samples were deemed to be adequate for analysis. The expression profiles of primary ovarian HGSC compared with normal ovarian tissue were significantly consistent with those of recurrent ovarian HGSC compared with normal ovarian tissue (correlation coefficient = 0.81, P = 0.0078). Among 31 miRNAs that increased by more than 4-fold in primary tumors compared with normal ovarian tissue, 27 were also significantly increased in recurrent tumor samples. Likewise, among 35 miRNAs that decreased by more than 4-fold in primary tumors compared with normal ovarian tissue, 34 were also significantly decreased in recurrent tumor samples. We identified 60 miRNAs that were significantly increased in recurrent serous ovarian carcinoma compared with primary tumor tissue, including miR-630, miR-370, and miR-575. Additionally, 52 miRNAs were significantly decreased in recurrent samples, including miR-509-3p, miR-514a-3p, and miR-506-3p. Our results demonstrate that primary and recurrent ovarian HGSC displayed similar miRNA expression patterns. Nevertheless, altered miRNA expression could be implicated in the recurrence of ovarian HGSC, and further study is needed to validate these data in independent cases using a homogeneous methodology.